Electrospray Ionisation Mass Spectrometry Facilitates Detection of Fibrinogen (Bβ 14 Arg → Cys) Mutation in a Family with Thrombosis - Brennan, Stephen O; Hammonds, Bruce; Spearing, Ruth; George, Peter M (Thrombosis and Haemostasis, 1997)
We report the first direct detection of a fibrinogen mutation by electrospray ionisation mass spectrometry. The propositus, from a family with a history of thrombosis, came to attention after a pulmonary embolism subsequent to a spontaneous abortion. Prolonged thrombin (41 s) and reptilase times (26 s) together with an impairment of fibrinopeptide B release suggested a mutation at the thrombin cleavage site of the Bβ chain. Direct mass analysis of purified fibrin chains from a thrombin induced clot showed that 50% of the Bβ chains remained uncleaved. The measured mass of the mono sialo isoform of this uncleaved chain was 54150 Da, compared to a value of 54198 Da for normal Bp chains. This decrease of 48 Da in the intact protein is indicative of either a Bβ 14 Arg to Cys, or Arg to Leu substitution. Heterozygosity for the Bβ 14 Arg → Cys mutation was verified by PCR amplification and DNA sequence analysis.